Crystallization and prevention of supercooling of microencapsulated n-alkanes - Zhang, Xing-xiang; Fan, Yao-feng; Tao, Xiao-ming; Yick, Kit-lun (Journal of colloid and interface science, 2005)
Microencapsulated n-alkanes ( n-octadecane, n-nonadecane, and n-eicosane) were synthesized by in situ polymerization using urea–melamine–formaldehyde polymer as shells. Microcapsules 5.0 and 10.0 wt% of 1-tetradecanol, paraffin, and 1-octadecanol were used as nucleating agents. The fabrication was characterized using Fourier transform infrared, light microscopy, and scanning electron microscopy. The crystallization and prevention of supercooling of the microcapsules are studied using differential scanning calorimetry (DSC) and wide-angle X-ray diffraction. The crystal system of the microencapsulated n-alkane is the same as that of the bulk. The enthalpies of the microcapsules containing 70 wt% n-alkanes are approximately 160 J/g. The melting temperature of the n-alkanes in the microcapsule is the same as that in the bulk. There are multiple peaks on the DSC cooling curves that are attributed to liquid–rotator, rotator–crystal, and liquid–crystal transitions. The DSC cooling behavior of microencapsulated n-octadecane is affected by the average diameters. The measured maximum degree of supercooling of the microencapsulated n-octadecane is approximately 26.0 °C at a heating and cooling rate of 10.0 °C/min. The degree of supercooling of microencapsulated n-octadecane is decreased by adding 10.0 wt% of 1-octadecanol as a nucleating agent.